2022
DOI: 10.3390/v14020312
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dynamics of SARS-CoV-2 Binding and Functional Antibodies upon BNT162b2 Vaccine: A 6-Month Follow-Up

Abstract: To investigate the dynamic association among binding and functional antibodies in health-care-workers receiving two doses of BNT162b2 mRNA COVID-19-vaccine, SARS-CoV-2 anti-RBD IgG, anti-Trimeric-S IgG, and neutralizing antibodies (Nabs) were measured in serum samples collected at 2 weeks, 3 months, and 6 months from full vaccination. Despite the high correlation, results for anti-RBD and anti-Trimeric S IgG were numerically different even after recalculation to BAU/mL following WHO standards indications. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
6
16
0
Order By: Relevance
“…Regardless of vaccine type, all participants presented with positive levels of antibodies 3 weeks after the second vaccination dose, which remained positive 3 months after the second vaccine. These results agree with other studies showing that antibody levels can indeed last for months following vaccination [ 10 , 11 , 12 , 13 , 14 ]. Additionally, our findings are in line with other similar international studies, highlighting the decline of S1RBD-specific antibodies over time [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regardless of vaccine type, all participants presented with positive levels of antibodies 3 weeks after the second vaccination dose, which remained positive 3 months after the second vaccine. These results agree with other studies showing that antibody levels can indeed last for months following vaccination [ 10 , 11 , 12 , 13 , 14 ]. Additionally, our findings are in line with other similar international studies, highlighting the decline of S1RBD-specific antibodies over time [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with other studies showing that antibody levels can indeed last for months following vaccination [ 10 , 11 , 12 , 13 , 14 ]. Additionally, our findings are in line with other similar international studies, highlighting the decline of S1RBD-specific antibodies over time [ 10 , 11 , 12 , 13 , 14 , 15 ]. Nevertheless, the immunogenic capacity of the antibodies present needs to be investigated further in order to determine their effectiveness in case of an infection with any of the emerging SARS-CoV-2 variants of concern.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Stamatopoulou et al, in a cohort of 142 infection-naïve healthcare workers, found that the total mean of anti-SARS-CoV-2 IgG levels decreased significantly four months following the second dose 21 . Also, Malipiero et al 22 and Matusali et al 23 , in health care workers who underwent COVID-19 vaccination, showed a marked decline in anti-RBD-IgG levels at six months. Padoan et al showed a reduction of 90% in anti-SARS-CoV-2 IgG antibody levels, which was independent of age, gender, and previous infection 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Nakagama et al [ 23 ] followed the convalescent phase of patients with COVID-19, measuring anti-RBD antibody titers using Elecsys ® Anti-SARS-CoV-2S (anti-RBD total Ig; Roche) and ARCHITECT SARS-CoV-2 IgG II Quantitative (Abbott) and indicated that the antibody titers measured by the Roche system were high avidity indices, and persisted even in the late convalescent period. Matusali et al [ 24 ] investigated the dynamic association among binding and functional antibodies in healthcare workers receiving the BNT162b2 mRNA COVID-19 vaccine. They compared anti-RBD using ARCHITECT SARS-CoV-2 IgG II Quantitative, and anti-Trimeric S-IgG by LIAISON SARS-CoV-2 TrimericS IgG (DiaSorin S.p.A.) and NAb.…”
Section: Discussionmentioning
confidence: 99%